Será um sonho pela metade? Reflexões e percepções sobre relações de gênero, raça e classe vivenciadas na formação e no espaço laboral de técnicas/os do eixo ambiente e saúde do IFPR - Incerti, Tânia Gracieli Vega (2022)
The research presented in this thesis aims to deepen and discover various knowledge regarding the discussion on gender relations in Vocational and Technological Education. Throughout the development of a master’s degree research, one could observe that the comprehension of the gender relations engaged in this space depended on the work with other categories, such as race and class, as well as the expansion of the research range to seek the perception of other participants, also part of the school community of the Federal Institute of Paraná – IFPR. Therefore, this research has the general objective of analyzing IFPR’s egress students’ perceptions of gender, race, and class relations, manifested in the process of professional education and its implications in the labor market. Hence, its participants are from Technological programs of the Axis Environment and Health of IFPR, which integrate this axis and are offered in the Curitiba and Londrina campuses. This research is qualitative, of descriptive/interpretive nature, carried out with two techniques for the construction of information: online questionnaire answered by 162 egress students who studied in the Technical in Nursing, Technical in Massage Therapy, Technical in Dental Prosthesis, Technical in Radiology and Technical in Oral Health at IFPR between 2015 to 2019, and a semistructured interview conducted with 20 participants of the previously mentioned programs. As main results we observed that the implications of gender, race and class relations are prominent in the workspace of these former students and are perceived by them. We highlight the relevance of this research by bringing to light the theoretical debate on the theme, still scarce in the institution, as well as presenting itself as a possible proposition of actions in the school space.